2019
DOI: 10.1002/stem.3009
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Reduction of Adverse Cardiac Scarring Facilitates Pluripotent Stem Cell-Based Therapy for Myocardial Infarction

Abstract: Pluripotent stem cells (PSCs) are an attractive, reliable source for generating functional cardiomyocytes for regeneration of infarcted heart. However, inefficient cell engraftment into host tissue remains a notable challenge to therapeutic success due to mechanical damage or relatively inhospitable microenvironment. Evidence has shown that excessively formed scar tissues around cell delivery sites present as mechanical and biological barriers that inhibit migration and engraftment of implanted cells. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 122 publications
(137 reference statements)
1
10
0
Order By: Relevance
“…In this study, we showed that the improvement of cardiomyocyte survival and vascularization in the infarcted hearts by hCVPCs and hNT‐3 are associated with the better cardiac function and reduced fibrosis formation. This is consistent with previous reports showing that anti‐apoptosis/necrosis of cardiomyocytes and/or improvement of angiogenesis can significantly reduce scar size in MI or I/R hearts 54,55 . Because MI and I/R cause apoptosis/necrosis of cardiomyocytes and destroy capillary networks, to rebuild vascular network after MI or I/R is essential for delivering oxygen and metabolites to cardiac cells to help recovery of damaged cells and thereby links to reduce scar size 1,54,56‐58 .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we showed that the improvement of cardiomyocyte survival and vascularization in the infarcted hearts by hCVPCs and hNT‐3 are associated with the better cardiac function and reduced fibrosis formation. This is consistent with previous reports showing that anti‐apoptosis/necrosis of cardiomyocytes and/or improvement of angiogenesis can significantly reduce scar size in MI or I/R hearts 54,55 . Because MI and I/R cause apoptosis/necrosis of cardiomyocytes and destroy capillary networks, to rebuild vascular network after MI or I/R is essential for delivering oxygen and metabolites to cardiac cells to help recovery of damaged cells and thereby links to reduce scar size 1,54,56‐58 .…”
Section: Discussionsupporting
confidence: 91%
“…rising number of pluripotent stem-cell-based therapies to treat myocardial infarction have been proposed. However, only marginal improvements in cardiac function have been reported from rodents to large animal models[47][48][49]. Here, we demonstrated (1) that the intramyocardial injection of 10 million early-stage hiPSC-CMs seven days after MI improved LV segmentary performance on infarcted rats.…”
mentioning
confidence: 66%
“…Understanding of the healing process of MI, including inflammatory, proliferative, and maturation phases, is important for design and timing selection of cell transplantation in patients. There exists a potential feedback loop (cell-cell interaction) between the host infarcted myocardium and the engraftment of implanted cells, as discussed by us [124]. In this section, we integrate the current evidence to speculate how ROS affect the cell survival and functional engraftment of implanted or regenerated CMs in the infarcted heart (Figure 3).…”
Section: Ros Affect Regenerative Therapy In the Infarcted Heartmentioning
confidence: 81%